Evaluation of the in vitro Activity and in vivo Efficacy of Anidulafungin-Loaded Human Serum Albumin Nanoparticles Against Candida albicans - Zhang, Yu; Liu, Yan-Chao; Chen, Si-Min; Zong, Hui; Hou, Wei-Tong; Qiu, Xi-Ran; Guo, Shi-Yu; Sun, Yu-Fang; Jiang, Yuan-Ying; An, Mao-Mao; Shen, Hui (Frontiers in Microbiology, 2021)
Recent decades have seen a significant increase in invasive fungal infections, resulting in unacceptably high mortality rates. Anidulafungin (AN) is the newest echinocandin and appears to have several advantages over existing antifungals. However, its poor water solubility and burdensome route of administration (i.e., repeated, long-term intravenous infusions) have limited its practical use. The objective of this study was to develop anidulafungin-loaded Human Serum Albumin (HSA) nanoparticles so as to increase both its solubility and antifungal efficacy. HSA was reduced using SDS and DTT, allowing liberation of free thiols to form the intermolecular disulfide network and nanoassembly. Reduced HSA was then added to MES buffer (0.1 M, pH 4.8) and magnetically stirred at 350 rpm and 25°C with AN (m/m 50:1) for 2 h to form nanoparticles (AN NP). We next performed routine antifungal susceptibility testing of Candida strains (n=31) using Clinical & Laboratory Standards Institute (CLSI) methodologies. Finally, the in vivo efficacy of both AN and AN NP was investigated in a murine model of invasive infection by one of the most common fungal species—C. albicans. The results indicated that our carrier formulations successfully improved the water solubility of AN and encapsulated AN, with the latter having a particle size of 29 ± 1.5 nm with Polymer dispersity index (PDI) equaling 0.173 ± 0.039. In vitro AN NP testing revealed a stronger effect against Candida species (n=31), with Minimum Inhibitory Concentration (MIC) values 4- to 32-fold lower than AN alone. In mice infected with Candida and having invasive candidiasis, we found that AN NP prolonged survival time (P<0.005) and reduced fungal burden in kidneys compared to equivalent concentrations of free drug (P < 0.0001). In conclusion, the anidulafungin nanoparticles developed here have the potential to improve drug administration and therapeutic outcomes for individuals suffering from fungal diseases.